Perbedaan Kepuasan Kerja Karyawan dalam Penerapan Perjanjian Kerja di PT TPCO PAN Asia Cabang Batam - Yessy Permata Donsari; Rusda Irawati (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2015)
This study aims examine the differences of job satisfaction between contract worker and permanent worker at PT TPCO Pan Asia, Batam. There are several variables that can affect job satisfaction, such as the satisfaction with the job, the work environment, leadership and company policies. 195 respondents consisting 41 contract worker and 154 permanent worker, were chosen using purposive sampling method. This data is analyzed using the Mann Whitney test. Results of analyzes generally show that there was no difference in job satisfaction of employees based on agreements between contract worker and permanent worker. As for specifically, differences based on variables that affect job satisfaction showed no difference to the work, the work environment and leadership between contract worker and permanent worker. While the difference of the job satisfaction about company policies showed significant difference. That is difference job satisfaction between contracts worker and permanent worker only in the company's policy about status of worker based on employmentagreement.